THE PROSPECTS OF THE DEVELOPMENT OF THE SYSTEM OF MULTICULTURAL EDUCATION - Vladimir N. Aniskin; Vladimir I. Bogoslovskiy; Tatiana A. Zhukova; Elena N. Ryabinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the problem of the development of the system of multicultural education. The stages of the development of the system of multicultural education are shown. The main stages of the process are: the improvement of the technologies of multicultural competence development and the components of the system of multicultural education. The specific features of the education technologies and the principles are described. Russian scientists have made a few advances in research regarding the development of multicultural competence. The technologies are applied in higher education. Although there is a growing interest in the role of these technologies, there is still a big amount of multicultural conflicts, ethnic and religious intolerance. Because of this, it is necessary to find the new mechanisms to improve the process of multicultural competence formation. It is important to underline the necessity to improve the process of cooperation between the universities of different countries. That influences the process of the development of the system of multicultural education as well as multicultural competence. As the importance of integration has risen, the number of comparative researches has to be enlarged. Their goal is to develop the views on the world educational process, to see the further tendencies of the national education system improvement. The lack of experience is considered as the problem of the process of multicultural education development. The article focuses on analyzing the role of synergetic approach, one on the conditions necessary for the development of foundations of the system of multicultural education.